Territory and population as elements of the political power in international relations - Isaković Zlatko (Međunarodni Problemi)
Parallel to the economic strength, military power, political system communication ability, ideology and morals, the significant elements of the political power are also the territory and population. Studying the influence of the territories and population on the political power of states the author points to the direction the transformation of these two phenomena will take place within the changed conditions of contemporary international relations.